Mitigation of Biofilm Formation on Corrugated Cardboard Fresh Produce Packaging Surfaces Using a Novel Thiazolidinedione Derivative Integrated in Acrylic Emulsion Polymers - Brandwein, Michael; Al-Quntar, Abed; Goldberg, Hila; Mosheyev, Gregory; Goffer, Moshe; Marin-Iniesta, Fulgencio; López-Gómez, Antonio; Steinberg, Doron (Frontiers in Microbiology, 2016)
Various surfaces associated with the storage and packing of food are known to harbor distinct bacterial pathogens. Conspicuously absent among the plethora of studies implicating food packaging materials and machinery is the study of corrugated cardboard packaging, the worldwide medium for transporting fresh produce. In this study, we observed the microbial communities of three different store-bought fruits and vegetables, along with their analog cardboard packaging using high throughput sequencing technology. We further developed an anti-biofilm polymer meant to coat corrugated cardboard surfaces and mediate bacterial biofilm growth on said surfaces. Integration of a novel thiazolidinedione derivative into the acrylic emulsion polymers was assessed using Energy Dispersive X-ray Spectrometry (EDS) analysis and surface topography was visualized and quantified on corrugated cardboard surfaces. Biofilm growth was measured using q-PCR targeting the gene encoding 16s rRNA. Additionally, architectural structure of the biofilm was observed using SEM. The uniform integration of the thiazolidinedione derivative TZD-6 was confirmed, and it was determined via q-PCR to reduce biofilm growth by 80% on tested surfaces. A novel and effective method for reducing microbial load and preventing contamination on food packaging is thereby proposed.